KETAHANAN UMKM OLAHAN SERBA IKAN DI KELURAHAN MARGODADI TERHADAP PANDEMI COVID 19 - Sholiha, Sangidatus Sholiha; Wibawa, Fajri Arif (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Indonesia ensuring the first case of coronavirus infection causes Covid-19 in early March 2020. Almost all sectors are affected, not only health. The economic sector has also been seriously affected by the corona virus pandemic. Micro, Small and Medium Enterprises (MSMEs) is also a result of this pandemic such as decreased income, labor, capital, production and distribution. This research aims at the resilience strategy of Micro, Small and Medium Enterprises (MSMEs) district Metro Pusat against the Covid-19 pandemic.OSERI in terms of decreased income, entry into work assignments, capital difficulties, the amount of stock / production of goods, distribution, to changes in the trade model from conventional to digital. Covid-19 is also MSME refugees to change strategies in trading, and strategies for living lifeKeywords: Micro, Small and Medium Enterprises (MSMEs), OSERI